2015
DOI: 10.1161/strokeaha.114.008260
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers, Pneumonia, and Outcome After Ischemic Stroke

Abstract: Background and Purpose-Increased sympathetic drive after stroke is involved in the pathophysiology of several complications including poststroke immunudepression. β-Blocker (BB) therapy has been suggested to have neuroprotective properties and to decrease infectious complications after stroke. We aimed to examine the effects of random pre-and onstroke BB exposure on mortality, functional outcome, and occurrence of pneumonia after ischemic stroke. Methods-Data including standard demographic and clinical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 26 publications
(28 reference statements)
4
47
3
4
Order By: Relevance
“…In contrast to our findings, Tziomalos and colleagues did not find a beneficial effect of ACEI or ARB therapy [36]. Similarly, Sykora and colleagues found improved in-hospital and 3-month AIS outcomes with the use of BB pre-stroke [37]. One important distinction from the current analysis is the duration of follow up; in our study, the duration of follow-up was significantly longer.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Tziomalos and colleagues did not find a beneficial effect of ACEI or ARB therapy [36]. Similarly, Sykora and colleagues found improved in-hospital and 3-month AIS outcomes with the use of BB pre-stroke [37]. One important distinction from the current analysis is the duration of follow up; in our study, the duration of follow-up was significantly longer.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, up to now, the longitudinal occurrence of troponin elevations in ICH patients was only insufficiently established and pathophysiological considerations further include an increase of intracranial pressure additionally triggering sympathetic storms [10,21,[24][25][26]. To protect patients with cerebrovascular diseases from this excessive stress, the use of beta-blockers is currently discussed [27,28]; however, this treatment is currently not considered in current guidelines for ICH-patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies, we found that baseline use of BBs was associated with a higher risk for infection. The previous 4 studies on BB treatment and infection risk reported that BBs were either associated with decreased infection risk or there was no association [4,5,8,9]. All studies had a retrospective study design and were heterogeneous with respect to stroke type (ischemic or hemorrhagic) and definitions of BB use (prior to stroke or after stroke admission) and infections.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, effects of BBs have been shown to be dose dependent, and dosage dependent effects could have been missed since the dosage of BB therapy was not controlled in this study [15]. Also, effects might differ between BBs already used prior to stroke, as compared to BBs started directly after stroke [5]. Only a randomized clinical trial could investigate the true potential of BB treatment for reducing stroke-associated infections, but the results of this study are not encouraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation